ONLINE ADVERTISING WEBSITE INSTALLATION PLACE WITH LANGUAGES PHP AND MYSQL PROGRAMMING - Suhartanto Suhartanto; Munich Heindari Ekasari, SKom, MMSI (Jurnal Sistem Informasi, 2009)
Today the Internet is growing very fast and wide, almost everyone in hemisphere wasalready familiar with the Internet, either directly or indirectly almost every day theyuse the Internet to meet their needs. Case This is a very big opportunity to takeadvantage of the Internet media as a tool to promote the product - the product of thecompany, entrepreneurs, shops and other forth. Internet media is a very effectivemedium compared with similar media because both cost and time required to makethese ads are relatively cheap and quick.At present, there are many sites - sites that provide facilities online advertising but themajority of the site - the site not offer it free or can be said to still pay.Starting from the opportunities that the authors mentioned above, the authors areinterested in designing and creating a site that provides a forum for online advertisingfree. These sites are www.narcisiklanonline.net16.net.